2003
DOI: 10.1002/bit.10700
|View full text |Cite
|
Sign up to set email alerts
|

Scalable inoculation strategies for microcarrier‐based animal cell bioprocesses

Abstract: Scalability is a major demand for high-yield, stable bioprocess systems in animal cell culture-based biopharmaceutical production. Increased yields can be achieved through high-density cell culture, such as in the combination of microcarrier and fluidized bed bioreactor technology. To minimize inocula volume in industrial applications of fluidized bed fermentation systems, it is crucial to increase the bed volume in the reactor during the fermentation process. We tested scale-up strategy for the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The macroporous gelatin microcarriers were shown to be effective for nasal chondrocyte expansion 22. Cytoline macroporous microcarriers were another class of materials tried in the cultivation of CHO cells by different researchers 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…The macroporous gelatin microcarriers were shown to be effective for nasal chondrocyte expansion 22. Cytoline macroporous microcarriers were another class of materials tried in the cultivation of CHO cells by different researchers 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…It is a readily available technology and scales up from T-flasks without difficulty. We have used this reactor on the 1 L scale to produce recombinant perilipin for further biophysical characterization (Londos et al, 2005;Tansey et al, 2004), but results in the literature indicate that it may be scalable (Dürrschmid et al, 2003;Griffiths, 2001). This system attains cell densities as high as those reported in the literature (10 7 cells/mL) at significant cost savings (Hu and Aunins, 1997).…”
Section: Culture Conditionsmentioning
confidence: 89%
“…Generally, the transfer of cells can be achieved by detachment of cells from confluent microcarriers and reattachment to freshly prepared bare ones (Cong et al 2001;Kong et al 1998) or by formation of cellular bridges between confluent and fresh microcarriers (Cherry and Papoutsakis 1988;Dürrschmid et al 2003). Wang and Fan (1999) found that the bead-to-bead transfer of Vero cells mainly followed the latter route, and the direct contact obtained by intermittent stirring could promote the formation of cellular bridges.…”
Section: Introductionmentioning
confidence: 97%